EB Ceiling Board - Ruslan, Muhamad Farihin Muzaqir; Muhammad Aizul Hakimi Razi; Muhammad Ikhwan Azmira; Siti Nooraiin Mohd Razali (Multidisciplinary Applied Research and Innovation, 2023)
The ceiling is part of the decoration in the construction of the house, the main use of the ceiling is to hide the bottom of the roof from the floor below. Asbestos is one of the most widely used materials by the ceiling manufacturing industry in Malaysia. Asbestos ceilings are an option for use by many communities in Malaysia today. However, the mixed elements used to produce ceilings such as asbestos has a fine dusts that corrode, fall, and fly in the air that very easily enter the human body and cause various diseases such as mesothelioma.. This problem is solved by replacing asbestos with egg boards and eggshells.